2004
DOI: 10.1158/1078-0432.ccr-03-0075
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive, Cytotoxic T Lymphocytes Specific for Peptides Derived from Normal B-Cell Differentiation Antigens in Healthy Individuals and Patients with B-Cell Malignancies

Abstract: Purpose: To investigate potential immunotherapeutic strategies in B lymphocytic malignancies we looked for CTLs recognizing CD19 and CD20 epitopes.Experimental Design: Three CD19 and CD20 peptides binding to HLA-A*0201 were identified and used to detect peptide specific CTLs by a quantitative real-time PCR to measure IFN-␥ mRNA expression in 23 healthy individuals and 28 patients (18 chronic lymphocytic leukemia (CLL), 7 follicular lymphoma, 2 acute lymphocytic leukemia, and 1 large cell lymphoma). Peptide-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Affinity-autoreactive cytotoxic T lymphocytes (CTLs) have already been described, especially against peptide CD19 or CD20 antigens. 52 These different strategies could apply to the ⌬CD20 protein. Based on our preliminary data for vaccination, in a transgenic murine model expressing human HLA, we have demonstrated that the splice junction area of the protein could be targeted to direct a specific CTL response, and that autoreactive CTLs against ⌬CD20 peptide junctions exist in healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…Affinity-autoreactive cytotoxic T lymphocytes (CTLs) have already been described, especially against peptide CD19 or CD20 antigens. 52 These different strategies could apply to the ⌬CD20 protein. Based on our preliminary data for vaccination, in a transgenic murine model expressing human HLA, we have demonstrated that the splice junction area of the protein could be targeted to direct a specific CTL response, and that autoreactive CTLs against ⌬CD20 peptide junctions exist in healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…CD40-B cells were generated as previously described (25). In brief, irradiated (75 Gy) human CD40L-transfected murine fibroblasts (LTK-CD40L), kindly provided by Dr. Van Kooten (Department of Nephrology, Leiden University Medical Centre, Leiden, Netherlands), were plated in six-well plates (BD Bioscience, Franklin Lakes, NJ) at a concentration of 0.1 × 10 6 cells/well, in RPMI complete medium [25 mmol/L HEPES buffer (pH 7.55), 2 mmol/L Lglutamine, 100 units/mL penicillin, and 100 μ/mL streptomycin; Life Technologies, Inc., Gaithersburg, MD] supplemented with 10% FCS and cultured overnight at 37°C, 5% CO 2 .…”
Section: Generation Of B-cell Linesmentioning
confidence: 99%
“…Studies suggest that CD8+ T cells may directly target lymphoma cells[31]. Higher stromal density of CD8+ T cells significantly predicted improved patient survival in our cohort of HIV-related DLBCL, independent of the IPI score.…”
Section: Discussionmentioning
confidence: 57%